PERLINDUNGAN HUKUM TERHADAP ASISTEN RUMAH TANGGA DITINJAU DARI UNDANG-UNDANG CIPTA KERJA - Nirmalah Nirmalah (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
So far, domestic workers do not have a legal umbrella to fight for the rights of decent workers. “In Indonesian culture, domestic workers are rarely called workers, but only helpers. This happens because there are many assumptions that domestic workers are in the informal sector, so they are reluctant to formally ask for the relationship between domestic workers and their employers. This situation results in an interpretation of whether domestic workers are included in the regulations regarding the rights of domestic workers. The problem in this research is what are the rights of domestic assistant workers under the job creation law and what are the forms of legal protection for domestic assistant workers in the job creation law. In this study using normative legal research methods with a normative juridical approach. The data collection in this study was carried out by means of library research on the relevant laws and regulations and analyzing the data qualitatively. From the results of this research, it can be concluded that the rights owned by workers and domestic workers above indicate a substantial difference in terms of legal protection. Specifically, the difference in legal protection lies in; protection of wages, protection of social security, protection of work safety, protection of occupational health, and protection against termination of employment. legal protection for domestic workers, both in the wage system, work safety, occupational health and social security programs for workers. Protection of Domestic Workers as regulated in the Regulation of the Minister of Manpower Number 2 of 2015